Pola Komunikasi Ibu Anak Pada Keluarga Buruh Migran Perempuan di Wonosobo, Jawa Tengah - Linus Kali Palindangan (Jurnal Komunikasi dan Bisnis, 2018)
Children are a blessing to the family. Therefore, they should be nurtured, well groomed and educated, and later, shall be able to contribute to their families, community, and nations. Family is the first place a child experiences education. In this case the role and function of parents in educating children becomes very important especially for the growth and development of children. But what happened to the family of female migrant workers in Tracap Village, Kaliwiro Wonosobo is very unique. A mothers who should stay home take care of children, instead going abroad and become migrant workers. This fact raises a question mark. How is the parent's communication pattern with her child intertwined? The purpose of this research is to know about parent communication pattern with children of the family of female migrant worker in Wonosobo and the impact of the communication pattern to the development of child's behavior and talent. This research is using qualitative research method. The data obtained through direct observation, interviews, documentation and literature study on women migrant workers from Wonosobo. After passing the data validity test by using data triangulation and data analysis technique through interactive process hence we can convey result of research as follows: 1) communication pattern between parent to their children in the family of female migrant worker in Tracap Village Kaliwiro Wonosobo is permissive communication pattern. 2) Such pattern of communication will have further affects on the formation of child unusual behavior and talent. An example is when a 8-year-old child whom never wear a clothes, and have no shame on doing so. Or the habit to eating white rice with raw water. Or drink raw water. Or other behavior in the form of taking his brother to take the neighbor's crop without feeling guilty when he was 10 years old.Anak merupakan berkat bagi keluarga. Oleh karena itu, anak harus dirawat, dididik dengan baik, agar kelak berguna bagi keluarga, masyarakat, bangsa dan negara. Keluarga adalah tempat paling pertama seorang anak mengalami pendidikan. Dalam hal ini peranan dan fungsi orangtua dalam mendidik anak menjadi sangat penting teristimewa bagi pertumbuhan dan perkembangan anak. Namun yang terjadi pada keluarga buruh migran perempuan di Desa Tracap Kaliwiro Wonosobo adalah sangat unik. Ibu yang seharusnya tinggal di rumah mengasuh anak, justru pergi ke luar negeri untuk menjadi buruh migran. Kenyataan ini menimbulkan tandatanya. Bagaimana pola komunikasi orangtua dengan anaknya terjalin. Tujuan penelitian ini adalah untuk mengetahui tentang pola komunikasi orangtua dengan anak pada keluarga buruh migran perempuan Wonosobo serta dampak pola komunikasi tersebut terhadap perkembangan perilaku dan bakat anak. Penelitian ini menggunakan metode penelitian kualitatif. Adapun data diperoleh melalui observasi langsung, wawancara, dokumentasi dan studi pustaka tentang buruh migran perempuan wonosobo. Setelah melalui uji validitas data dengan menggunakan trianggulasi data dan teknik analisis data melalui proses interaktif maka dapat kami sampaikan hasil penelitian seperti berikut ini: 1) pola komunikasi orangtua anak pada keluarga buruh migran perempuan di Desa Tracap Kaliwiro Wonosobo adalah pola komunikasi permisif. 2) Pola komunikasi yang demikian selanjutnya berdampak pada pembentukan perilaku dan bakat anak yang tidak wajar. Seperti tidak pernah memakai baju meskipun umurnya sudah 8 tahun tanpa malu sedikit pun. Atau terbiasa makan makanan berupa nasi putih disiram air mentah. Atau minum air mentah. Atau perilaku lain berupa mengajak saudaranya mengambil tanaman milik tetangga tanpa merasa bersalah padahal umurnya sudah 10 tahun